Ultrasonic tomography imaging for two-phase flow - Mohd Hafiz, Fazalul Rahiman; Ruzairi, Abdul Rahim; Mohd Hezri, Fazalul Rahiman; Mazidah, Tajjudin (Universiti Malaysia Perlis (UniMAP), 2010)
Real-time process monitoring is important in many areas of industry and scienti c research concerning liquid/gas two-phase ow, and is closely related to accurate measurement and control of hydrodynamic parameters such as ow regime and ow rate. Ultrasonic tomography has the advantage of imaging two component ows by providing quantitative and real-time data on media, without process interruption. It allows insight of the process, enables closed-loop control systems and is noninvasive and possibly non-intrusive. The overall anticipated e ects are improvements in product yield and uniformity, minimized input process material, reduced energy consumption and environmental impact, and lowering exposure to plant personnel. Ultrasonic tomography enables the measurement of certain characteristics of objects that cannot be easily obtained by other methods. Ultrasounds are able to detect changes in acoustic impedance which is closely related to the media density and complements other tomographic imaging technologies.